Climate Change and the Polanyian Counter-movement: Carbon Markets or Degrowth? - Stuart, Diana; Gunderson, Ryan; Petersen, Brian (New Political Economy, 2019)
In the midst of a wave of market expansion, carbon markets have been proposed as the best way to address global climate change. While some argue that carbon markets represent a modern example of a Polanyian counter-movement to the environmental crisis, we adopt a structural interpretation of Polanyi to refute this claim. Carbon markets represent a further expansion of markets that fails to address the underlying contradictions related to the commodification of nature. In addition, they increase risks to society and the domination of economic elites. While carbon markets further subject social and ecological relations to market mechanisms, we examine degrowth as a possible response to climate change that prioritises social and environmental goals over economic growth. While degrowth continues to be dismissed as impractical or impossible, a growing number of scholars, scientists and activists argue it is the only way to address global climate change. In contrast to carbon markets, we argue degrowth could represent a genuine Polanyian counter-movement in response to climate change. In addition, degrowth could help all those disenfranchised by market fundamentalism by addressing the triple crises related to the commodification of land, labour and money.
Keywords: carbon markets; carbon offsetting; climate; climate change; degrowth; economic development; economic elites; emissions (air pollution); environment; environmental studies